Peran BNN Kota Kendari DalaM Penanggulangan Penyalahgunaan Lem FOX Pada Kalangan Remaja Perspektif Maqasid Syariah ( Studi di Kecamatan Kadia Kota Kendari) - Muliani Muliani; Aris Nur Qadar Ar Razak (QAIMUDDIN: Journal of Constitutional Law Review, 2022)
This study aims to determine the role of Kendari City National Narcotics Agency in overcoming the abuse of Fox glue among adolescents from the perspective of Maqasid Syariah. This research is a type of empirical normative legal research. Data collected through observation, interviews, and documentation. The results of the study show that. First, the role of the Kendari City National Narcotics Agency in efforts to overcome the abuse of Fox glue among teenagers is divided into 2, namely 1) Preventive efforts, Examples of preventive efforts are a) Socialization in the community and in the educational environment. b) Cooperation with the Kendari City Regional Government. 2) Repressive efforts, for example, by carrying out medical rehabilitation for fox glue abusers. Second, Maqasid Syariah Perspectives on the role of Kendari City BNN in overcoming the abuse of Fox glue among teenagers. 1) Conducting socialization using the lecture method, this is in line with the purpose of Islamic law, namely to maintain religion, 2) Conducting medical rehabilitation for abusers of fox glue to treat souls and minds that have been damaged due to misuse of fox glue, this is in line with the objectives of Islamic law namely to maintain the soul and mind 3) Coordinate with the local government and the issuance of the mayor's circular, namely the prohibition of selling fox glue to children, this is in line with the purpose of Islamic law, namely to maintain property.